Rural Energy Conditions in Oyo State: Present and Future Perspectives on the Untapped Resources - Popoola, Ayobami Abayomi; Magidimisha, Hangwelani Hope (International Journal of Energy Economics and Policy, 2019)
Over 60% of the Nigeria population still resides within the rural spaces. These rural spaces are zones of isolation with yet high electricity and energy demand for enhanced livelihood and settlement liveability. Despite the demand for electricity in these rural areas, it still remains under-serviced as far as accessibility to stable electricity supply is concerned; likewise connection history to conventional electricity grid is many rural areas remains a mirage. With rural energy resource potentials untapped, this study made use of both qualitative and qualitative data gathered across 472 rural households in 9 randomly selected rural local government areas (LGAs) to provide a narrative into the rural household energy experiences. The study brings to light the abundance of the unutilized renewable resources that can be utilized towards providing electricity for rural households. Limitation identified includes weak political will, limited profit orientation of electricity investors and limited energy choice information to households. Keywords: Electricity; Renewable energy; Rural households JEL Classifications: O18, Q42, Q43 DOI: https://doi.org/10.32479/ijeep.7558